Digital technology and the subjects of literacy and mathematics in the preschool atelier - Magnusson, Lena O (Contemporary Issues in Early Childhood, 2023)
In this article, the focus is on the entangled relations between digital technology, art activities, mathematics, literacy and children in Swedish preschool ateliers. As part of an ethnographic study, the researcher follows how children use digital technologies and non-digital materials (such as shells, pens, paper, wood, bubble wrap and light) to create and make the visual and aesthetic aspects of the technology seen. In the analysis of the children’s play-based and art-oriented activities in the atelier, the subjects of literacy and mathematics become visible. The analytical approach includes the use of sociocultural theory and multimodal theory, and looking at mathematics in accordance with the six organising principles described by Alan Bishop. The results show that the children’s activities with digital technology and non-digital artefacts appear to activate, expand and transform their understanding and use of literacy and mathematics.